Effect of the meter square ultra-high density planting technology on growth, yield and phyto-nutritional composition of Moringa oleifera - Magabe, Realeboga Carley (My University, 2025)
Moringa oleifera Lam., is a versatile, nutrient-dense crop that has drawn a lot of interest due to its ability to combat hunger and food insecurity. Despite many uses of Moringa oleifera, little is known about how ultra-high density planting (ultra-HDP) technology affects its growth, yield, nutrition and phytochemical composition. The aim of this study was to develop scientific information on how meter square ultra-HDP technology would affect growth and yield attributes (plant height, stem diameter, leaf yield), nutrition (proximate, mineral and amino acid composition) and phytochemical (total phenols, total carotenoids, antioxidant activity and Ultra-Performance Liquid Chromatograph Mass Spectrometer (UPLC-MS) untargeted polar metabolites) attributes in both young and mature leaves of M. oleifera. An experimental trial was established in an open field condition to accommodate four planting densities: ultra-HDP (10 x 10 cm), high (30 x 30 cm), medium (50 x 50 cm), and conventional (100 x 100 cm) in a Randomized Complete Block Design (RCBD) with three replications. During growth of seedlings, growth parameters including plant height and stem diameter, were recorded weekly. At harvest (Week 18) some growth, yield and physico-chemical components such as leaf yield, root length, root-to-shoot ratio, chlorophyll SPAD index, proximate composition, amino acids, minerals, bioactive compounds antioxidants (total phenols, total carotenoids, antioxidants activity: , 2-diphenyl-1-picrylhydrazyl (DPPH), 2,2'-Azinobis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS), and Ferric Reducing Antioxidant Power (FRAP), and UPLC-MS untargeted polar metabolites were determined. Data were analyzed using Statistix 10.0, with mean separation by Least Significant Difference on growth and yield parameters and Tukey’s Honestly Significant Difference on all other evaluated parameters at a 5% significance level. The results revealed that ultra-HDP (10 x 10 cm) significantly (p ≤ 0.05) enhanced leaf yield per meter square in comparison to other densities. However, this outcome was influenced by the unequal number of plants per metre square, with ultra-HDP having the highest plant density. While ultra-HDP increased total leaf yield, the conventional density (100 x 100 cm) achieved superior growth parameters, including stem diameter, plant height, Conventional density also attained higher plant leaf yield (390.7 ± 1.59 g) and some nutrients such as calcium (1.22 ± 0.02%), potassium (2.38 ± 0.01%), and glutamic acid (4.88 ± 0.04%) when compared to the other studied densities. In contrast, ultra-HDP favored zinc accumulation. Young leaves exhibited higher protein (28.36 ± 0.1%), carbohydrates (43.52 ± 0.2%), and essential amino acids, including leucine and phenylalanine, while mature leaves were richer in fat. The results further revealed that young leaves grown at conventional density contained higher levels of protein (31.00 ± 0.01%), carbohydrates and essential amino acids, such as histidine (0.77 ± 0.02%), arginine (2.62 ± 0.04%), threonine (1.63 ± 0.04%), and lysine (2.11 ± 0.03%). In contrast, young leaves under ultra-HDP showed significantly elevated proline levels (1.46 ± 0.01%), likely as a response to stress. Untargeted metabolites, total phenols content, total carotenoids, and antioxidant activity were also evaluated and compared across all planting densities. Methanol extracts were analyzed for untargeted metabolites using UPLC-ESI-QTOF-MS. Untargeted metabolite profiling identified 96 polar analytes, including members of the glucuronic acids, flavonoid-O-glycosides, and terpene glycosides. Principal component analysis (PCA) revealed distinct clustering of metabolites based on planting density and leaf age. Ultra-high density enhanced the accumulation of flavonoids, such as quercetin derivatives, which significantly contributed to antioxidant activity. Ultra-high density elevated total phenols content (1260.9 ± 3.12 mg GAE/g ) compared to 804.6 ± 1.98 mg GAE/g under conventional density. Additionally, antioxidant activity, as determined by DPPH, ABTS, and FRAP assays, increased under ultra-HDP giving a result of 51.96 ± 0.4, 3.85 and 0.29 ± 0.01 μmol TE/g DW respectively. Flavonoids were identified as the primary contributors to total antioxidant activity, with ultra-HDP promoting the accumulation of most metabolites including kaempferol derivatives, quercetin 3-O-(6''-acetyl-glucoside), quercetin 4'-glucoside and rutin. This study highlights the potential of ultra-HDP to optimize M. oleifera cultivation by improving both yield and nutritional quality, particularly zinc content, while enhancing the concentration of bioactive metabolites. Additionally, the study demonstrated that ultra-high density planting and young leave markedly increased the concentrations of phytochemicals, such as total phenols, total carotenoids, and antioxidant activity, which are non-nutritive substances with significant antioxidant and medicinal qualities. These results have great potential to advance sustainable farming methods and encourage the wider use of M. oleifera as a nutrient- and phytochemical-rich crop for food and medicinal applications.
Thesis (M. Agricultural Management (Plant Production)) -- University of Limpopo, 2025
Keywords: None-Nutritive substances; Moringa oleifera; Phyto-nutritional; Ultra-high density; Moringa oleifera; Food -- Composition; Food security